[Engineering students in computer lab, circa 1980-1995] (1989)
Two students seated in computer lab. Student on the left is wearing a 'Wave Tools' (surfboard company established in 1969) sweater. The students appear to be working with graphic and fractal design. See also ITS 90-003.